PENGETAHUAN DAN SIKAP REMAJA TERHADAP TANAMAN OBAT TRADISIONAL DI KABUPATEN BULELENG DALAM RANGKA PELESTARIAN LINGKUNGAN : SEBUAH KAJIAN EKOLINGUISTIK - Rasna, I Wayan (Bumi Lestari Journal of Environment, 2010)
This study aims at investigating: (1) adolescent lexical knowledge about traditional medicinal plants from ecolinguistic perspective and (2) adolescent attitude toward traditional medical plants and its effect on ecology and ecolinguistics as an effort at preserving environment and lexis of medicinal plants. This study was conducted to 125 adolescents in Buleleng regency in 25 villages in 9 districts. The data were obtained through interview, observation, and lexical competence test. The data were processed descriptively. The result shows that the adolescent lexical knowledge about traditional medicinal plants is as follows. 28 rural adolescents (37.33% ) has an adequate knowledge , 47 (62.66%) an inadequate knowledge and 9 urban adolescents (18%) an adequate knowledge, 38 (76%) an inadequate knowledge and 3 ( 6%) a low level of knowledge. Ecolinguistically, this has an effect on reduction of lexical forms on the part of the adolescents. Fourty percent of the adolescent attitude showed disagreement with the assumption of backwardness and low opinion about the users of the traditional medicinal plants this is a positive attitude of the adolescents and is a good asset in the effort at developing faithful attitude, pride and awareness of the use of medicinal plants to preserve the ecology and ecolinguistics.
Keywords: knowledge; attitude; medicinal plants; ecolinguistics